Conflicts and Adaptions: How to Display the Art of the Soviet Period - Helme, Sirje (Actual Problems of Theory and History of Art, 2020)
In 2006, a new main building (named Kumu) of the Art Museum of Estonia was opened. Creating a new permanent exhibition, museum confronted by the question how to show Estonian art from the Soviet times as exceptional period in our art history, intertwined with the topics of power and imposed-upon art ideologies. We have tried to find an answer to this question twice by now (in 2006 and 2016).The article is about two different ways of creating the exposition, although the basis of both of them is the issue of the relations between art and politics. The first display strongly marked the power lines, separated periods and emphasised their differences. The new permanent display is more ambivalent and discursive, taking into consideration the attitudes of the younger generation towards the long-ago period. Our art history at the time was divided into three distinctive histories. First, the works that could be shown to the public, which nevertheless contained independent national and social-critical approaches. Second, the works that were never displayed for the general public. Third, the art of those who escaped in 1944 to the West and continued living there as artists at the first opportunity.All this together constitutes our art history, although it is not easy to tie it together, and it is even more difficult to present it in a museum as spatial and temporal consensus.
Keywords: Art Museum of Estonia (KUMU); Estonian art; collection; exhibition; Soviet art